Elevation change and stability on a prograding delta. Issue 4 (22nd February 2017) - Wagner, Wayne; Lague, Dimitri; Mohrig, David; Passalacqua, Paola; Shaw, John; Moffett, Kevan
Abstract: Coastal wetland systems are among the most dynamic landscapes on Earth's surface; however, interrelated processes create wetland platforms that are relatively constant in space and time. Theoretically, "stable" elevations should maintain themselves through time if the balance of processes creating that elevation remains unchanged. At Louisiana's prograding Wax Lake Delta, we measure landscape change between 2009 and 2013, quantifying volumetric changes to the delta, subaerial slope adjustment, and an equilibrium elevation of 0.56 m North American Vertical Datum of 1988 (where elevation change, on average, is zero), around which elevations fluctuate. We calculate a system average "equilibrium time scale" of 16 years to describe how long locations will take to approach the stable elevation. This time scale increases as a function of distance from channel edge. Peaks in elevation probability density functions can form for multiple reasons and do not require stability; e.g., peaks can temporarily form at elevations where elevation change rate is locally minimum. Key Points: The subaerial Wax Lake Delta is aggrading toward a stable elevation on a time scale of 16 years Higher elevations of the delta fluctuate around equilibrium as change is episodic, not continuous Peaks in elevation distributions do not necessarily indicate corresponding elevation equilibria